1995
DOI: 10.21273/hortsci.30.5.940
|View full text |Cite
|
Sign up to set email alerts
|

Thermomorphogenic Responses in Stem and Leaf Development

Abstract: correlated with the difference between DT and NT (DIF) rather than the actual DT/NT under which plants are grown when temperatures range from 10 to 26C (Erwin, 1991; Erwin et al., 1989b; Moe and Heins, 1990; Moe et al.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
1
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 48 publications
3
41
1
1
Order By: Relevance
“…4; Erwin and Heins, 1995; Grindal, 1997; Vaagen et al , 2003). The negative DIF treatment reduced chlorophyll content in both genotypes and in all leaves of the pea plants.…”
Section: Discussionmentioning
confidence: 99%
“…4; Erwin and Heins, 1995; Grindal, 1997; Vaagen et al , 2003). The negative DIF treatment reduced chlorophyll content in both genotypes and in all leaves of the pea plants.…”
Section: Discussionmentioning
confidence: 99%
“…Plant growth is reduced under abnormal thermoperiodic conditions, i.e. lower temperatures during the light period than during the dark, a condition known as negative DIF (difference between day temperature and night temperature) that is exploited for control of plant stature [200]. Stavang et al [201] showed that stems of pea plants grown in negative DIF contained lower concentrations of C 19 -GAs and increased expression of PsGA2ox2 compared with plants grown in positive DIF and suggested that this gene was a major target for this response.…”
Section: Figure 5 Regulation Of Seed Germination In Arabidopsis By Rementioning
confidence: 99%
“…For this reason, other environmentally-friendly and low-cost alternatives should be explored. Increasing experimental evidence shows that more precise physiological knowledge of how environmental variables such as temperature and light modulate phenology and plant growth is a pre-requisite for designing cultivation practices to produce high quality plants (Erwin and Heins, 1995;Casal et al, 2004).…”
mentioning
confidence: 99%